From biomass waste to biofuels and biomaterial building blocks. (October 2016) - Liu, Chun-Min; Wu, Shu-Yii
Abstract: Concerns about the earth's sustainable management and the reduction of greenhouse gas emissions have become an important issue in the world. One of the alternative solutions is producing biofuels and biomaterial building blocks from biomass waste. Biomass wastes, which include solid waste of agricultural residues (rice straw, wet birch pulp), agro-industrial wastes (mushroom waste, cotton cellulose) and liquid waste of food and related industrial wastewater are abundant feedstock for renewable biohydrogen, biomethane and biochemicals productions etc. This technology of waste to energy and biochemicals includes the pretreatment of biomass, subsequently converted to sugars (hydrolyzate). Sugars are thereafter transformed into biofuels such as hydrogen, methane, ethanol, and the biomaterial building blocks such as volatile fatty acids: Lactic acid, Acetic acid, Propionic acid, and Butyric acid etc. This study proposes an integrated two-stage continuous system to produce biohydrogen and biomethane at higher yields, whilst removing more COD from the wastewater. Highlights: Biofuels and biomaterial building blocks from biomass waste. Two-stage of biohydrogen and biomethane production. High value added products production by biomass.